Integrated Transcriptome and Targeted Metabolome for Resolving Flavonoid Biosynthesis in Figs (Ficus carica Linn.) - Junting Sun; Hadir Yishake; Ming Wang; Hao Zhang; Jie Yan (Biology)
Figs are an edible and medicinal plant rich in polyphenols and flavonoids with unique pharmacological effects. However, the mechanism of flavonoid synthesis in figs is not clear. In this study, fig fruits of six varieties were collected for RNA sequencing and UPLC-MS data collection. The results showed that a total of 39 differential metabolites were identified by targeted metabolomics, and their contents were determined by UPLC-MS. The clustered heat map analysis showed that most of the differential metabolites were highly accumulated in BRD and FY. A total of 62 flavonoid biosynthesis pathway genes were identified by transcriptome analysis, and FcCHS, FcCHI, FcFLS, FcCYP, and FcDFR were the key genes identified for the accumulation of flavonoids and flavonols in the dark-colored varieties. In addition, a total of 1671 transcription factor genes, mainly MYBs, bHLHs, and AP2/ERFs, were identified. This study will enrich the transcriptomic data of figs and provide some help in resolving the synthesis mechanism of fig flavonoids.